Use of the Internet of Things in the Business Environment to Smart Business - Húdik Martin; Koman Gabriel; Imppola Jorma Jaakko; Vodák Josef (Logi, 2019)
The article discusses the use of Internet of Things (hereinafter as IoT) solutions in the social and business environment to support managerial decision-making in Smart businesses. The paper key objective is to assess the rate of increasing technological advancement of the IoT which already affects us all, so it is not possible to talk about the IoT as a matter of the future. Currently, modern technologies provide specific level of digitization of business processes. Due to the penetration of information and communication technologies (hereinafter as ICT) in all areas of social life and business processes, it is possible to implement decisions on product production based on customer needs and requirements. This trend is mainly due to technological advances in ICT and the Internet. Thanks to the internet and the phenomenon called Internet of Things, it is possible to achieve higher profits and improve the quality of life in society. The manuscript main findings can be summarized through a statement that all the businesses try to implement the concept of IoT in their processes, and thus they become smart businesses. Thanks to IoT, businesses can quickly process data and distribute the results to responsible people for decision-making in the enterprise.